Proceedings of the 2nd International Conference on Bioelectromagnetism (Cat. No.98TH8269)
DOI: 10.1109/icbem.1998.666463
|View full text |Cite
|
Sign up to set email alerts
|

Effective bioimpedance spectroscopy method for evaluation of body cell water compartments

Abstract: The traditional Cole or CFC basic model might offer too coarse estimations in personalized lhaemodialytic treatment. To take advantage of the full information content offered by BIS ins$rumentation the traditional CFC model can be extended into a more convenient model: the Extended CFC (ECFC) model. The ECFC model is used to fit raw bioimpedance measurements to increase the overall estimation accuracy of Rlesistance and Reactance terms. An experimental comparison between CFC, ECFC model simulations, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
2
5
1
Order By: Relevance
“…3-5). Similar results were reported by Fiorini et al [1998], who found at least a 10-fold accuracy improvement with the ECFC model. Although the ECFC model reproduced the experimental data better, there was still The unusual behavior observed in our experimental data could be due to a number of causes, such as, polarization phenomena from the skin-electrode interaction, the inductance of the conductors and/or the natural inductance of biological cells and body tissues.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…3-5). Similar results were reported by Fiorini et al [1998], who found at least a 10-fold accuracy improvement with the ECFC model. Although the ECFC model reproduced the experimental data better, there was still The unusual behavior observed in our experimental data could be due to a number of causes, such as, polarization phenomena from the skin-electrode interaction, the inductance of the conductors and/or the natural inductance of biological cells and body tissues.…”
Section: Discussionsupporting
confidence: 91%
“…However, some studies show an unusual behavior on its experimental data, which cannot be explained or reproduced through theoretical predictions obtained by Cole and Cole [1941] [Khaled et al, 1995;Rigaud et al, 1995;Fiorini et al, 1998]. Our experimental data show this unusual behavior, which was observed for frequencies below a threshold (Table 1; .…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…It is a paper on impedance fitting using the well known theories of Macdonald [1992]. Fiorini et al [1998] propose the ECFC model, with an inductor. However, there is no change in the sign of the ''experimental'' data that they provide nor a decrease in the real part at low frequencies.…”
Section: (D) Supporting Referencesmentioning
confidence: 99%